DETERMINAÇÃO DE CONTAMINANTES EMERGENTES E AVALIAÇÃO DE SEU COMPORTAMENTO EM AMBIENTES AQUÁTICOS: USO DE SISTEMAS MODELO - MIRANDA, LUCIANE (2017)
Pharmaceuticals compounds comprise a group of compounds considered to be contaminants of emerging concern (CECs) in environmental matrices. Determinations of CECs are usually performed by chromatographic methods, which require several pretreatment steps of the sample demanding time and supplies. Thus the present work proposed the development and validation of a voltammetric methods to quantify nimesulide (NIM) and streptomycin (STP) in aqueous samples and also to evaluate the behavior of the drugs NIM, STP and alprazolam (ALP) in the environment. The methodology for the determination of ALP had previously been optimized by the LabGATI research group. Initially, the voltammetric parameters were optimized using square wave adsorptive voltammetry for STP and differential pulse for NIM, from the voltammograms profile and the intensity of the response (peak current). Then, the adequacy of the analytical method was evaluated using validation criteria, such as precision, selectivity, linearity, limits of detection and quantification. The linearity was evaluated by standard addition curve in the concentration range of 8.09 to 210.4 μg L-1 to STP and 0.5 to 130 μg L-1 of NIM. The limits of detection (LOD) were 0.18 μg L-1 to STP (with 180 s of accumulation) and 0.15 μg L-1 to NIM (60 s of accumulation). The accuracy and precision of each method was expressed as percent recovery of STP and NIM in fortified solutions, and showed deviations below 20%, acceptable according to criteria proposed for analytes at trace levels, indicating the good precision and accuracy of the methods. The proposed voltammetric methods have advantages over others already described in the literature, since they do not require steps of pre-treatment of the samples, thus speeding fast and low cost analyzes when compared to other methods used in the quantification of these drugs. NIM was detected in samples of wastewater at concentration from 101.7 to 385.0 μg L-1, in three samplings. However, STP was not detected, in any of sample. Degradation studies were performed on little scale to STP, NIM and ALP, in laboratory under controlled conditions, with natural and artificial radiation. The behavior of the drugs under radiation showed the rapid degradation of STP with 3 h of exposition to UV radiation, indicating that this drug is quite photosensitive. On the other hand, NIM degraded with 12 h of radiation and ALP with 18 h, so it was the most resistant. The degradation of NIM and ALP with solar radiation occurred in 125 and 212, respectively. Other factors such as concentration of the drug, the presence of suspended particulate matter in the matrix were also evaluated in the tests under controlled conditions and to propose possible behaviors of them in the aquatic environment.